2019
DOI: 10.1111/1750-3841.14934
|View full text |Cite
|
Sign up to set email alerts
|

The Phenolic Compounds, Metabolites, and Antioxidant Activity of Propolis Extracted by Ultrasound‐Assisted Method

Abstract: The influences of ultrasound-assisted, pharmacopeia, and supercritical fluid extraction methods on bioactive compounds and biological activities of propolis were evaluated. Results showed that propolis extracted by ultrasoundassisted method contained more phenolic compounds, and showed the highest total phenolic content (245.84 ± 6.41 mg GAE/g DW), total flavonoids content (198.82 ± 5.74 mg RE/g DW), and stronger in vitro antioxidant activity (DPPH·: 1.03 ± 0.04 mmol Trolox/g DW, ABTS+·: 2.19 ± 0.05 mmol Trolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
2
25
1
Order By: Relevance
“…al, 2019). In a similar to our studies, chrysin was found one of the major phenolic compounds by ultrasound-assisted extraction (Yuan et al, 2019). In their study, pinocembrin, chrysin, and pinobanksin were found as 30.96, 30.56 and 29.97 mg/g respectively.…”
Section: The Individual Phenolic Compounds Of the Propolis Extractssupporting
confidence: 90%
“…al, 2019). In a similar to our studies, chrysin was found one of the major phenolic compounds by ultrasound-assisted extraction (Yuan et al, 2019). In their study, pinocembrin, chrysin, and pinobanksin were found as 30.96, 30.56 and 29.97 mg/g respectively.…”
Section: The Individual Phenolic Compounds Of the Propolis Extractssupporting
confidence: 90%
“…Peaks 12 and 18 were identified as 3-O-acetyl-pinobanksin ( m / z = 313.0612) and 3-O-butyryl-pinobanksin ( m / z = 341.0917), respectively, based on fragment ions, molecular ions, and the literature [ 37 ]. From the results and previous data [ 38 ], the main flavonoids of propolis extract were identical to chrysin (30.56 ± 0.60 mg/g DW), pinocembrin (30.96 ± 0.34 mg/g DW), galangin (16.69 ± 0.45 mg/g DW), and pinobanksin (9.56 ± 0.25 mg/g DW; Figure 2 ).…”
Section: Resultssupporting
confidence: 80%
“…Following the initial LC-MS/MS method development with the seven standards, an ultrasound-assisted ethanol extract was tested to tentatively identify other precursor ions from other abundant compounds. Based on this analysis and a comparison to several other published lists of propolis components [33][34][35][36][37][38][39], seventeen more standards were purchased from Sigma-Aldrich (Mississauga, ON, Canada). All twenty-four standards (including gallic acid) were tested by LC-MS/MS on the quadrupole-Orbitrap and by infusion on a linear quadrupole ion trap mass spectrometer (LTQ-XL, Thermo-Fisher Scientific, San Jose, CA, USA).…”
Section: Identification Of Chemical Compounds In Propolis From Eastern Canada Obtained Following Se Mae and Uaementioning
confidence: 99%